Diffuse endoscopically visible, predominantly low grade dysplasia in Barrett’s esophagus (with video) - Tsoi, Edward H.; Fehily, Sasha; Williams, Richard; Desmond, Paul; Taylor, Andrew (Endoscopy International Open, 2019)
Background Low grade dysplasia (LGD) in Barrett’s esophagus (BE) has generally been considered as undetectable endoscopically.Aim To describe a phenotype which consists of diffuse, endoscopically visible, predominantly low grade dysplasia in Barrett’s esophagus (DEVLB), with often subtle but visible endoscopic changes seen with high definition white light (HDWL) and narrow-band imaging (NBI).Method A systematic search of a prospectively collected database for patients satisfying predefined criteria for DEVLB and a review of endoscopic and histological features of biopsies and endoscopic mucosal resection (EMR) specimens.Results Out of a total of 419 patients referred to our expert center for assessment of dysplastic Barrett’s esophagus during the period January 2009 to March 2018, there were 7 patients (1.7 %) who satisfied the criteria defined for DEVLB, identified on their initial assessment endoscopy. All patients were treated by EMR of visible abnormal mucosa during their assessment endoscopy at our tertiary referral center. There was a total of 47 EMR specimens obtained, with a median of 6 (IQR 5–9) EMR resection pieces per patient, of which 36 (77 %) contained LGD, 8 (17 %) high grade dysplasia (HGD), 2 (4 %) non-dysplastic Barrett’s esophagus (NDBE), and 1 (2 %) contained early esophageal adenocarcinoma (EAC).Conclusion DEVLB is a distinct phenotype seen in a small but significant proportion of individuals with dysplastic Barrett’s esophagus. Patients with DEVLB have widespread LGD, with many having areas of focal HGD or early cancer within this area. We believe these patients are best treated with extensive EMR of the visibly abnormal area.